1997
DOI: 10.1074/jbc.272.10.6167
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Alcohols and Anesthetics with Protein Kinase Cα

Abstract: Nature 364, 82-84). In this study, we show that interaction of n-alkanols and general anesthetics with PKC␣ results in dramatically different effects on membraneassociated compared with lipid-independent enzyme activity. Furthermore, the effects on membrane-associated PKC␣ differ markedly depending on whether activity is induced by diacylglycerol or phorbol ester and also on n-alkanol chain length. PKC␣ contains two distinct phorbol ester binding regions of low and high affinity for the activator, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
89
3
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(106 citation statements)
references
References 40 publications
13
89
3
1
Order By: Relevance
“…While we have not mapped the specific phosphorylation site(s), as short term viability of primary colonocytes precludes high specific labeling of c-Src with [ 32 P]orthophosphoric acid, a dephosphorylation of Src at tyrosine 527 is likely involved in its activation (25,31). The additional finding that immunoprecipitated Src was stimulated by 1␣,25(OH) 2 D 3 incorporated into liposomes, suggests that this secosteroid may also directly activate the kinase, perhaps by an allosteric mechanism similar to that observed for PKC (27), and proposed as a mechanism for Src activation by the EGF receptor, independent of Src dephosphorylation (26). While the present studies in rat colonocytes indicate that Src activation induced by 1,25(OH) 2 D 3 involves, at least in part, tyrosine dephosphorylation, the specific role of allosteric alterations in this activation will require further study.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…While we have not mapped the specific phosphorylation site(s), as short term viability of primary colonocytes precludes high specific labeling of c-Src with [ 32 P]orthophosphoric acid, a dephosphorylation of Src at tyrosine 527 is likely involved in its activation (25,31). The additional finding that immunoprecipitated Src was stimulated by 1␣,25(OH) 2 D 3 incorporated into liposomes, suggests that this secosteroid may also directly activate the kinase, perhaps by an allosteric mechanism similar to that observed for PKC (27), and proposed as a mechanism for Src activation by the EGF receptor, independent of Src dephosphorylation (26). While the present studies in rat colonocytes indicate that Src activation induced by 1,25(OH) 2 D 3 involves, at least in part, tyrosine dephosphorylation, the specific role of allosteric alterations in this activation will require further study.…”
Section: Discussionmentioning
confidence: 72%
“…In this regard, 1,25(OH) 2 D 3 , when incorporated into liposomes, has also been shown to directly activate PKC, a serine/threonine kinase (27). We therefore studied the ability of 1,25(OH) 2 D 3 to directly activate c-Src which had been isolated by immunoprecipitation from unstimulated colonocytes.…”
Section: 25(oh)mentioning
confidence: 99%
“…However, halothane, another volatile anesthetic, has been shown to stimulate the activity of purified brain PKC in the presence of physiologically relevant lipid bilayer vesicles (Hemmings et al, 1995). In addition, Slater et al (1993) suggested that PKC contains a hydrophobic binding site for alcohols and anesthetics in the regulatory region of PKC, and they observed that the activity of purified PKC␣ was increased by long-chain n-alkanols (Slater et al, 1997). However, a more recent study suggests that alcohols may activate PKC␣ not by direct binding to PKC but by altering lipid structure and by enhancing PKC-lipid bilayer binding (Shen et al, 1999).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown that rat brain PKC activity is inhibited by 1-O-alkylglycerol (51,52) and stimulated by 1-O-alkyl-2-acylglycerol (53), two potential metabolites of 1-O-alkyl-2,3-diacylglycerol. Interestingly, medium-chain fatty alcohols (C8-C10) either inhibit or enhance PKCa activity in a complex manner, but the effects of longer chain alcohols, which accumulate in SLS cells, have not been studied (54). Therefore, it is intriguing to speculate that two of the lipids (or their metabolites) that accumulate in SLS keratinocytes might influence PKC activity and interfere with certain steps in cell differentiation.…”
Section: Discussionmentioning
confidence: 99%